Checkpoint inhibitors in lung cancer: latest developments and clinical potential. (November 2016) - Schvartsman, Gustavo; Ferrarotto, Renata; Massarelli, Erminia
Lung cancer is the leading cause of cancer death in the United States. The vast majority of patients are diagnosed with metastatic disease with a 5-year survival rate of less than 5%. After first-line chemotherapy or biomarker-matched targeted therapy, only suitable for a small group of patients, further systemic therapy options rendered very limited, if any, benefit until recently. Checkpoint inhibitors have significantly improved outcomes in patients with metastatic non-small cell lung cancer (NSCLC) and are currently an established second-line therapeutic option. In this manuscript, we review the mechanism of action of checkpoint inhibitors, present the available data with approved and experimental agents, discuss the progress that has already been made in the field, as well as toxicity awareness, and future perspectives.